Artificial Ripening: What We are Eating (Journal of Medicine, 2008)
In recent times there is much concern about artificial ripening of fruits in many parts of the world including Bangladesh. Large amount of tropical fruits are produced in Bangladesh. Though fruits like mango naturally ripen in trees; some chemicals are used to ripen them artificially which hasten the ripening process. Ripe fruits are not suitable to carry & distribute as they get rotten. So fruit traders pick unripe fruits & use certain methods to increase the shelf life of them. For many years Ethylene had been used as a fruit ripening agent. But nowa- days Calcium carbide is getting popular in this regard as it has a faster ripening property. But inappropriate use of Carbide to ripen fruits is associated with many health hazards. In this topic we have tried to reveal the essentials of this burning issue & looked for solutions.     DOI = 10.3329/jom.v9i1.1425 J MEDICINE 2008; 9 : 42-44